Physical Function, An Adjunct to Brain Health Score for Phenotyping Cognitive Function Trajectories in Older Age: Findings From The Irish Longitudinal Study on Ageing (TILDA) - Kenny, Rose; Williamson, Wilby; Hernndez, Belinda (My University, 2022)
Background: Evidence is limited regarding the cumulative effect of risk factors on cognitive decline and the added value of physical function for cognitive function trajectory stratification. We operationalize 13 modifiable dementia risk factors in a scoring system and investigate the relationship between this brain health score, combined with simple measures of physical function, and risk of cognitive decline. Methods: Population-based cohort study of persons aged 50 and older from the Irish Longitudinal Study on Ageing without a history of dementia at baseline who underwent repeated neuropsychological tests (8.08 ± 0.3-year follow-up) were included in the analyses. Exposures were the number of brain health metrics (defined by the Lancet Commission on Dementia Prevention, Intervention, and Care report) at recommended optimal levels. Physical function exposures included Timed Up and Go, dual-task walking speed, and grip strength. Each health metric and physical function measure at the recommended level was assigned a value of 1 and combined to generate brain health scores. Relationship with group-based trajectories of global cognitive function (multidomains composite score), estimated using K-means for longitudinal data, was assessed via ordinal logistic regressions. Results: Among 2 327 participants (mean age, 61 years; 54% women), each additional optimal metric on the brain health score (odds 0.67 [0.62, 0.73]) was associated with reduced odds of cognitive decline. Adding Timed Up and Go (odds 0.71 [0.59, 0.84]) and dual-task walking speed (odds 0.74 [0.63, 0.89]) further improved model fit (ΔAIC = 14.8). Conclusion: These findings support the promotion and maintenance of physical function in addition to brain health strategies to reduce the risk of cognitive decline.
PUBLISHED
Keywords: Cognitive decline, Dual-task walking speed, Heart–brain axis, Risk factors, Timed Up and Go; Ageing; AGEING